Molecularly Grafted MWCNT-g-PCL Networks: Unveiling Structural Synergy in PEG/PANI Nanocomposite Films - Kavum, Ahmet Yusuf; Pekdemir, Mustafa Ersin; Qader, Ibrahim Nazem; Orman, Yusuf (Wiley, 2026)
Polymer nanocomposites that combine biodegradable, biocompatible matrices with conductive fillers are increasingly important for advanced flexible electronics and biomedical applications. However, conventional binary polymer systems often face trade-offs in mechanical strength, thermal stability, and electrical functionality. To address this challenge, we developed a novel ternary nanocomposite by grafting polycaprolactone (PCL) onto hydroxyl-functionalized multi-walled carbon nanotubes (MWCNT-OH) via ring-opening polymerization, then blending with polyethylene glycol (PEG) and polyaniline (PANI). The resulting MWCNT-g-PCL/PEG/PANI films, containing 1-10 wt% PANI, integrate biodegradability with tunable conductivity. Structural characterization (FTIR, XRD) confirms successful PANI incorporation without disrupting the semicrystalline PCL/PEG matrix. Thermal analysis indicates improved stability: the initial degradation temperature rose from similar to 200 degrees C in the binary blend to similar to 240 degrees C with 10 wt% PANI, accompanied by higher char residue. A slight increase in melting point (71 degrees C to 73 degrees C) at the highest PANI loading suggests enhanced crystallite stability. Dielectric spectroscopy revealed that the base blend's dielectric constant (epsilon ' similar to 3.9 at 10 Hz) initially decreases with 1%-4% PANI, then rebounds at 10% PANI (approaching the pristine value) due to the formation of conductive networks at a percolation threshold. The dielectric loss factor (epsilon '') peaked at intermediate PANI content but dropped at 10% PANI, and AC conductivity reached similar to 10(-5) S/cm at high frequency-an order-of-magnitude improvement. In conclusion, transitioning from binary to ternary blends yields a multifunctional composite with enhanced thermal endurance and tailorable electrical properties, all achieved without compromising the polymer's crystallinity, highlighting its potential for high-performance, sustainable polymer-based electronics, sensors, and biocompatible coatings.
Keywords: dielectric properties; MWCNT-g-PCL; polyaniline (PANI); ring-opening polymerization; thermal stability